Evaluation of solubility and partition properties of ampicillin-based ionic liquids - Florindo, Catarina
In order to overcome the problems associated with low water solubility, and consequently low bioavailability of active pharmaceutical ingredients (APIs), herein we explore a modular ionic liquid synthetic strategy for improved APIs. Ionic liquids containing L-ampicillin as active pharmaceutical ingredient anion were prepared using the methodology developed in our previous work, using organic cations selected from substituted ammonium, phosphonium, pyridinium and methylimidazolium salts, with the intent of enhancing the solubility and bioavailability of L-ampicillin forms. In order to evaluate important properties of the synthesized API-ILs, the water solubility at 25 degrees C and 37 degrees C (body temperature) as well as octanol-water partition coefficients (K-ow's) and HDPC micelles partition at 25 degrees C were measured. Critical micelle concentrations (CMC's) in water at 25 degrees C and 37 degrees C of the pharmaceutical ionic liquids bearing cations with surfactant properties were also determined from ionic conductivity measurements. (C) 2013 Elsevier B.V. All rights reserved.